Factors that influence brand equity of sport shoes product among UiTM students / Muhammad Naim Zulkifli - Zulkifli, Muhammad Naim (Faculty of Business and Management, 2016)
Brand equity can be assumed as the feelings, thoughts and also images perceived by the consumers once they interact with the brand. Hence, it is important in having good brand equity as company tends to generate higher profit from good relations made with the consumers. This thesis is conducted to investigate the relationship between four factors which are brand association, brand loyalty, brand awareness and brand image with brand equity of sport shoes. This is because there was no latest research study conducted to analyse the brand equity of sport shoe. Researches from previous study on brand equity have stated that four independent variables that are related with brand equity were brand association, brand loyalty, brand awareness and also brand image. The objective of the research study was to investigate the relationship between four factors which are brand association, brand loyalty, brand awareness and brand image with brand equity of sport shoes. Besides that, this research also tends to investigate the most influential factors in influencing brand equity towards sports shoes. This research entitled ―Factors That Influence Brand Equity among Students from Faculty of Business Management in UiTM Kampus Bandaraya upon Sport Shoes’ Brand. Research study had been conducted to obtain results and findings. There was a list of 317 respondents that were involved in answering the questionnaires that had distributed to them. There were available sources data from previous research had been used as references to understand the issues or matters arise in the research study. This research concludes with discussion on the results, study limitation and recommendation for future research.